Pokémon origami : fold your own Alola region Pokémon - Baur, Wolfgang (Writer on fantasy games); Mitchell, David (Pikachu Press, The Pokémon Company International, 2017)
Provides detailed directions for creating ten origami Pokémon, including Pikachu, Rowlet, and Popplio.